Does Secondary Smoking and Posyandu Affect the Risk of Hypertension in Pregnancy? Multilevel Evidence from Magelang, Central Java - Erin Rizkiana; Uki Retno Budihastuti; Vitri Widyaningsih (Masters Program in Public Health, 2019)
Background: Pregnancy hypertension was a complication of pregnancy which became one of the causes of maternal and perinatal morbidity and mortality in the world. This study aimed to determine the effect of individual and contextual factors of integrated health post (posyandu) on hypertension in pregnancy.Subjects and Method: A case control study was conducted in 5 posyandus in Magelang, Central Java, from April to May 2019. A sample of 210 women was selected by simple random sampling. The dependent variable was hypertension in pregnancy. The independent variables were age, parity, nutritional status, family history of hypertension, history of hypertension before pregnancy, history of hormonal contraceptive, and exposure to cigarette smoke. The data were collected by questionnaire and analyzed by a multilevel multiple logistic regression.Results: Hypertension in pregnancy increased with age <24 or > 35 years old (b= 2.10; 95% CI= 0.16 to 4.04; p= 0.033), parity (b= -3.81; 95% CI = - 6.31 to -1.32; p = 0.003), nutritional status (b= 3.35; 95% CI= 1.36 to 5.33; p= 0.001), family hypertension history (b= 3.35; 95% CI= 1.33 to 5.37; p= 0.001), hypertension history before pregnancy (b= 2.46; 95% CI= 1.1 to 3.81; p<0.001), hormonal contraceptive history (b= 2.6; 95% CI= 0.53 to 4.72; p= 0.014), and cigarette smoke exposure (b= 2.87; 95% CI= 1.15 to 4.58; p= 0.001). Posyandu had negligible contextual effect on hypertension in pregnancy with ICC= 7.6%.Conclusion: Hypertension in pregnancy increases with age <24 or > 35 years old, parity, nutritional status, family hypertension history, hypertension history before pregnancy, hormonal contraceptive history, and cigarette smoke exposure. Posyandu has negligible contextual effect on hypertension in pregnancy.Keywords: Hypertension, pregnancy, cigarette smoke, multilevel analysisCorrespondence: Erin Rizkiana, Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: erinrizkiana777@gmail.com. Mobile: 085729883106Journal of Epidemiology and Public Health (2019), 4(3): 247-258https://doi.org/10.26911/jepublichealth.2019.04.03.12